اللغة العربية بإندونيسيا (السياسة، التاريخ، الوضع الحالي - khoirurrijal khoirurrijal (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2017)
The Arabic language is spoken by Indonesian society as well as being religious language in the Holy Qur’an. The prestige of this noble life to ensure its existence since the early days of their entry to Indonesia with the simultaneous introduction of Islam. Conclusion of this research can be described as follows: (a). The Arabic language education in Indonesia "religious political question" about the history of the spread of the Islamic faith of Indonesia, (b). history reminds us that there is an old business relationship between Indonesians and two Arab started since the third century AD. and spread the Arabic language significantly after the advent of Islam the beginning of the connection between the Arabic and Indonesian. Finally, became the Arabic words in the Indonesian language as verbally, structures, semantics and sounds, and (c). the methods of teaching Arabic in Indonesia are such as: Directly, audio-verbal, analysis of the sentence and selectivity.